Quality Assessment of Local Apples (Malus Domestica) Packaged and Treated with Chitosan During Refrigerated Storage - Asal, Khalid. N.; Ammar Waleed Taha (American Journal of Botany and Bioengineering, 2026)
This study was conducted in a refrigerated warehouse in Salah al-Din Governorate after harvesting uniform apples (in terms of shape and size) free from any damage from an orchard in Balad District on August 7, 2024. The apples were stored for six months under controlled temperature and humidity. The aim of the study was to evaluate the performance of chitosan and the different types of packaging used with the Ibrahimi apple variety during the storage period. Data were recorded on December 7, 2024, the results, after statistical analysis, indicated that using chitosan at a concentration of (2) ml.L-1 resulted in a significant increase in most of the studied traits compared to the control treatment. Vacuum-sealed polyethylene packaging significantly outperformed other packaging methods in sugar content, TSS, percentage of dry matter, acidity, and protein. The interaction between chitosan at a concentration of 2 ml.L-1 and vacuum-sealed polyethylene packaging yielded the best results for most of the studied traits. Proline content was unaffected by the study factors and their interaction.